Behaviour of Cadmium(II) Ions on Cation-Exchange Resins - Sevgi Kocaoba (Adsorption Science & Technology)
Cadmium is one of the most toxic heavy metals known and is considered inessential for living organisms. This element is found at low concentrations in natural environments, but human activities have led to increased levels in all continents. In the present study, the removal of cadmium(II) ions from aqueous solutions was investigated. Experimental investigations were undertaken using the ion-exchange resins Amberlite IR 120 (strongly acidic), Amberlite IRC 718 (weakly acidic and chelating), Lewatit TP 207 (weakly acidic and chelating) and Lewatit CNP 80 (weakly acidic). For investigations of the exchange equilibria, different amounts of resin material were contacted with a fixed volume of a cadmium ion-containing solution. Because the uptake of cadmium ions was mainly dominated by the pH of the liquid phase, the pH value was varied between 0 and 3 with sample sizes of 0.5–5.0 g in each series studied. The initial and final cadmium ion concentrations were measured by ICP–AES methods. Exchange equilibria were evaluated for strongly and weakly acidic resins via the surface complex formation theory that considers the sorption of ions as a local equilibrium reaction caused by the amphoteric behaviour of the surface. Application of this theory to exchange equilibria with ordinary and chelating weak acid exchange resins capable of releasing protons led to a comprehensive description of the systems. Binary equilibria were described by a logarithmic equilibrium parameter that was a linear function of the resin phase. For the evaluation of the equilibrium parameters, the generalized separation factors were calculated from the experimental data and plotted against the respective dimensionless resin loadings. Linear relationships were obtained in most cases although systematic deviations were found for small loadings.